SCIENTIFIC-PROJECT CONSULTING AS AN INNOVATIVE FORMAT OF POSTGRADUATE EDUCATION - G. A. Ignatieva; O. V. Tulupova (Obrazovanie i Nauka, 2017)
Introduction. Today the main social and economic advantage of Russia in global economy (we do not take natural wealth into account) is the human capital which development has to become a priority for all levels of an education system. The relevance of the article determined by the need to modernize the educational programs, technology and content of the educational process in the institutional space of postgraduate teacher education. It is one of the key factors in the development of the intellectual capital of a society, providing a transition to continuous, socially oriented, associated with global and domestic fundamental science education for all people and aimed at the formation of the creative socially responsible personality. The new mission of post-degree training «through all life», consisting in the advancing formation of intellectual potential of the country, demands search of new forms and methods of additional professional education.Aim. The aim of the article is to disclosure the essence of scientific-project consulting as an innovative format of teachers and scientific-pedagogical staff.Methods. The institutional approach is the basis of the study. In accordance with this approach, the development strategy and the areas of work of traditional and new institutions of post-degree education – Department of Pedagogy and Andragogy and the Center of Scientific and Design Consulting are designated. As methodological base of this type of consulting, it is offered to use provisions of the genetic-substantial theory of the developing education, in particular the principle of development regulating processes of continuous improvement of professionalism of experts of education and development of new functions by them in post-industrial society.Results. The conceptual model of a reflexive outline of management of process of formation of new professional positions of the teacher is constructed; its components are characterized. Scientific-project consulting as a backbone concept of model is defined as a specific innovative format of preparation of pedagogical and academic-teaching personnel capable to conscious design and transformation of own professional activity and education in general acts. Projecttransformative approach to implementation of analytical, organizational-administrative and scientific-methodical support of teachers concludes in the mechanism of realization of such consulting. The value of this format of additional professional education from the point of view of the joint practice-focused scientific search organization of the solution of problems in education system is shown. The forms of post-degree training which are most demanded within scientific and design consulting are described. Scientific novelty. In the field of pedagogical post-degree education consulting has not become a full standard rule yet. In general, educational consulting including development of techniques of management and planning of educational activity is applied to methodical maintenance of functioning and development of educational structures. Perspective scientific and project types of consulting in post-industrial society still have remained out-of-sight of a scientific pedagogical research. The authors of the present article make one of the first attempts on completion of this gap in the Russian education.Practical significance. Introduction of scientific-project consulting in the field of post-degree training of the top skills for the sphere education offers new opportunities of scientific-organizational and expert-consulting maintenance of innovative activity of members of an educational process.